1976
DOI: 10.1093/jnci/56.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tumors in the Dunkin-Hartley Guinea Pig 2 3

Abstract: Seventy-nine spontaneous neoplasms in Dunkin-Hartley guinea pigs were observed over a 9-year period in the Fort Detrick guinea pig colony. Sixty-three of the neoplasms were found during approximately 8,500 necropsies performed on animals under 27 months of age. The remaining 16 tumors were in 34 breeders maintained after 27 months of age on a natural life-span study. Of this group, 10 (29.4%) developed neoplasms by the termination of the study, when the animals were 80 months of age. The skin tumor, trichofoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
5

Year Published

1978
1978
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
13
0
5
Order By: Relevance
“…While Rogers and Blumenthal (1960), Ediger and Kovatch (1976) and Field et al (1989) investigated the occurrence of spontaneously arising tumours in thousands of laboratory guinea pigs, the present study reports tumours of the cervix and uterus in guinea pigs kept as pets. Genital polyps are rare in most species of small mammals and rodents, except in rats where they are the most common uterine neoplasm (Goodman and Hildebrandt, 1987a, b;Eiben and Bomhard, 1999).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…While Rogers and Blumenthal (1960), Ediger and Kovatch (1976) and Field et al (1989) investigated the occurrence of spontaneously arising tumours in thousands of laboratory guinea pigs, the present study reports tumours of the cervix and uterus in guinea pigs kept as pets. Genital polyps are rare in most species of small mammals and rodents, except in rats where they are the most common uterine neoplasm (Goodman and Hildebrandt, 1987a, b;Eiben and Bomhard, 1999).…”
Section: Discussionmentioning
confidence: 68%
“…In the current study, eight polyps were observed in the genital tract of guinea pigs. These were not mentioned in earlier surveys (Rogers and Blumenthal, 1960;Ediger and Kovatch, 1976;Sommerey, 2001).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations